2023
DOI: 10.1038/s41598-023-29820-5
|View full text |Cite
|
Sign up to set email alerts
|

Early sleep after action observation and motor imagery training boosts improvements in manual dexterity

Abstract: The systematic observation and imagination of actions promotes acquisition of motor skills. Furthermore, studies demonstrated that early sleep after practice enhances motor learning through an offline stabilization process. Here, we investigated behavioral effects and neurodynamical correlates of early sleep after action observation and motor imagery training (AO + MI-training) on motor learning in terms of manual dexterity. Forty-five healthy participants were randomized into three groups receiving a 3 week i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…However, because the performance of observed and unobserved sequences was tested in different groups of participants, and baseline performance testing by necessity affords actual physical practice, the effect of group differences (at baseline) could not be ruled out. Further support for a possible beneficial effect of early post-training sleep in training by observation, comes from a recent study of participants undergoing multiple sessions (3 weeks) of video-clip based action observation training (additional mental imagery practice was included) 26 . It was found that manual action observation training (the video-clips observed in training presented transitive daily tasks performed with the right upper limb) had improved the participants’ manual dexterity (tested in tasks other than the tasks used in training) and that the gains in manual dexterity were larger for participants trained at evening (followed by early sleep) compared to those undergoing the same training at least 12 h before sleeping 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because the performance of observed and unobserved sequences was tested in different groups of participants, and baseline performance testing by necessity affords actual physical practice, the effect of group differences (at baseline) could not be ruled out. Further support for a possible beneficial effect of early post-training sleep in training by observation, comes from a recent study of participants undergoing multiple sessions (3 weeks) of video-clip based action observation training (additional mental imagery practice was included) 26 . It was found that manual action observation training (the video-clips observed in training presented transitive daily tasks performed with the right upper limb) had improved the participants’ manual dexterity (tested in tasks other than the tasks used in training) and that the gains in manual dexterity were larger for participants trained at evening (followed by early sleep) compared to those undergoing the same training at least 12 h before sleeping 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Further support for a possible beneficial effect of early post-training sleep in training by observation, comes from a recent study of participants undergoing multiple sessions (3 weeks) of video-clip based action observation training (additional mental imagery practice was included) 26 . It was found that manual action observation training (the video-clips observed in training presented transitive daily tasks performed with the right upper limb) had improved the participants’ manual dexterity (tested in tasks other than the tasks used in training) and that the gains in manual dexterity were larger for participants trained at evening (followed by early sleep) compared to those undergoing the same training at least 12 h before sleeping 26 . However, each time-of-day condition was tested in a different group of participants, and, as the authors acknowledge, the potential influence of circadian rhythms on observation or motor imagery could not be ruled out.…”
Section: Introductionmentioning
confidence: 99%
“…To date, sleep-dependent effects have been mainly investigated after a training based on motor practice 23 , 25 . Moreover, literature data have investigated upper limb dexterity changes induced by the observation with or without imagination of motor tasks, revealing higher benefits when the training sessions were followed by an early sleep-window 26 29 . Therefore, when considering the current background, it is reasonable to speculate that sleep might enhance the acquisition of trained motor skills such as gait and balance abilities, when occurring immediately after AOMI training sessions in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, differently from most existing studies in the field, we evaluated brain electrical activity during the execution of a complex visuomotor integration task, i.e. the Nine Hole Peg Test (NHPT), which requires the continuous processing of visual information to control the performance of fine movements [17,18]. Moreover, the current study is the first, to our knowledge, to examine frequency-dependent modulations in brain functions triggered by visuomotor integration processes using spontaneous EEG data from a large dataset, i.e.…”
Section: Introductionmentioning
confidence: 99%